2007
DOI: 10.1160/th06-07-0373
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic action of tranexamic acid in hereditary haemorrhagic telangiectasia (HHT): Regulation of ALK-1/endoglin pathway in endothelial cells

Abstract: Recurrent epistaxis is the most frequent clinical manifestation of hereditary haemorrhagic telangiectasia (HHT). Its treatment is difficult. Our objective was to assess the use of tranexamic acid (TA), an antifibrinolytic drug, for the treatment of epistaxis in HHT patients and to investigate in vitro the effects of TA over endoglin and ALK-1 expression and activity in endothelial cells. A prospective study was carried out on patients with epistaxis treated with oral TA in the HHT Unit of Sierrallana Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 40 publications
3
60
0
6
Order By: Relevance
“…Antifibrinolytic agents, such as -aminocaproic or tranexamic acids, systemically administered have produced satisfactory results with an improvement in epistaxis and the associated anemia and with an increase in the transcriptional activity of ENG and ALK1 promoters (Fernandez et al, 2007;MoralesAngulo et al, 2007). However, contraindications appear in those patients prone to suffer thrombosis; hence, it is necessary to screen the HHT population for high levels of coagulant factors VIII and V and von Willebrand factor before Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antifibrinolytic agents, such as -aminocaproic or tranexamic acids, systemically administered have produced satisfactory results with an improvement in epistaxis and the associated anemia and with an increase in the transcriptional activity of ENG and ALK1 promoters (Fernandez et al, 2007;MoralesAngulo et al, 2007). However, contraindications appear in those patients prone to suffer thrombosis; hence, it is necessary to screen the HHT population for high levels of coagulant factors VIII and V and von Willebrand factor before Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of vascular alterations, telangiectases are very sensitive to slight traumata and even to the air when breathing, which gives rise to nose bleeds. Many different therapies have been assayed, but none of them with conclusive results, such as the antibrinolytic agents -aminocaproic or tranexamic acids (Fernandez et al, 2007;Morales-Angulo et al, 2007) or therapy based in hormones. Estrogens like raloxifene, a selective estrogen receptor modulator, at doses used for oral contraception may eliminate bleeding in women symptomatic for HHT, as we have published previously (Albiñ ana et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic manipulation of coagulation and fibrinolytic pathways is often employed to try to limit blood loss in HHT 41,42,181,182 . These therapies have not yet been supported by data from randomized controlled trials.…”
Section: Antifibrinolytics and Prothrombotic Agentsmentioning
confidence: 99%
“…High proportion without medical or ENT review 33,34 . New data: Surgery and embolization [35][36][37][38][39] ., medical treatments 31,[40][41][42][43][44][45] …”
Section: New Data On Echo Grading and Predictive Valuesmentioning
confidence: 99%
“…Indeed, we cannot rule out the possibility that other factors important for insulin might be also affected in Eng +/2 mice. In this regard, a comparative gene expression analysis revealed that in endothelial cells from HHT1 patients, 20% of the deregulated genes (down or upregulated) respect to cells from healthy subjects were involved in general metabolism [22]. Among these genes it is worth mentioning the presence of several members of the solute carrier (SLC) protein family.…”
Section: Discussionmentioning
confidence: 99%